Growth, flowering fruit set and yield in some cultivars/selections of walnut (Juglans regia) - PANDEY, CHANDRA; TOMAR, C S (The Indian Journal of Agricultural Sciences, 2012)
Nine cultivars of walnut (Juglans regia L.) were evaluated during 2007–08 for growth, flowering fruit set and yield characters. Comprehensive observations on growth, foliage, floral characters and yield were recorded for each cultivar/ selection and considerable variation was observed among the cultivars for these characters. Tree height, trunk girth, tree volume and shoot extension growth ranged from 24.64 to 51.10 cm, 12.31 to 37.39 cm, 11.89 to 28.05 m3 and 29.68 to 65.14 respectively. Time of male and female flowering varied from last week of March to second week of April. All the cultivars exhibited protandry. Fruit set, fruit retention and yield varied from 19.74 to 60.57%, 25.29 to 50.82% and 0.77 to 2.15 kg/tree. Cultivar Paynee was found superior to all the cultivars and recorded maximum height, girth, tree volume, fruit set, fruit retention and yield.